Ramon Llull, The book of the order of chivalry. Trad. by Noel Fallows, The Boydell Press, New York, 2013; 102 pp. - Luna Mariscal, Karla Xiomara (El Colegio de México, 2016)
Se reseñó el libro: The book of the order of chivalry